Synthesis, Photophysical Properties, and Metal-Ion Recognition Studies of Fluoroionophores Based on 1-(2-Pyridyl)-4-Styrylpyrazoles - Orrego-Hernández, Jessica (ACS Omega, 2019)
[Image: see text] A convenient access toward novel fluoroionophores based on 1-(2-pyridyl)-4-styrylpyrazoles (PSPs) substituted at position 3 with donor or acceptor aryl groups is reported. The synthesis proceeds in two steps: the first one via Wittig olefination of the appropriate 4-formylpyrazole and then Mizoroki–Heck coupling to yield the desired products in an overall yield of up to 69%. Photophysical properties of products (4-styryl) and their intermediates (4-vinyl) were explored, finding that they have strong blue-light emission with high quantum yields (up to 66%) due to ICT phenomena. The 3-phenyl PSP was studied as a turn-off fluorescent probe in metal ion sensing, finding a high selectivity to Hg(2+) (LOD = 3.1 × 10(–7) M) in a process that could be reversed with ethylenediamine. The sensing mechanism and binding mode of the ligand to Hg(2+) were established by HRMS analysis and (1)H NMR titration tests.